Compounding material, method of preparing compounding material, method of producing cured body, and cured body
By crushing incineration ash to expose latent hydraulic substances and control pozzolan-reactive material reactions, the blended material promotes rapid curing in hardened concrete, addressing the issue of slow strength development in conventional concrete materials.
Patent Information
- Application Number
- JP2023110737
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-05
- Publication Date
- 2025-01-20
AI Technical Summary
The performance of hardened concrete, particularly the speed at which compressive strength increases with age, is influenced by the materials used, necessitating a compounding material that enhances this performance.
A blended material comprising incineration ash, such as sewage sludge incineration ash, is prepared by crushing to expose latent hydraulic substances, inhibiting pozzolan-reactive material reactions to promote rapid curing reactions, thereby accelerating strength development in hardened concrete.
The method accelerates the onset and progression of curing reactions, improving compressive strength from immediate post-mixing to predetermined ages, reducing delays and enhancing concrete performance.
Smart Images

Figure 2025008508000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention particularly relates to a mixing material to be mixed into a hardened concrete body, a method for preparing the mixing material, a method for producing the hardened concrete body, and the hardened concrete body. [Background technology]
[0002] Industrial by-products such as fly ash, ground granulated blast furnace slag, and silica fume are used as mixing materials such as admixtures added to hardened concrete. In addition, in order to make more efficient use of resources and reduce waste, it is expected that incineration ash derived from waste will also be used as a mixing material for concrete with or without Portland cement (hereinafter simply referred to as "concrete").
[0003] These mixing materials include latent hydraulic substances (hereinafter referred to as "latent hydraulic materials") that are used according to the volume or weight of the cement to be mixed, or to replace part of the cement to be mixed, and pozzolanic reactive substances (hereinafter referred to as "pozzolanic reactive materials"). Furthermore, some mixing materials have both latent hydraulic properties and pozzolanic reactivity by utilizing the physicochemical properties of the admixture as it hardens. In addition, mixing materials include polymers intended to improve functionality after hardening, and expansive materials intended to prevent and suppress cracks in the hardened body due to hardening and shrinkage after hardening. These compounding materials can be mixed alone or in any combination, and can be made into a hardened material by adding water alone or water and an alkaline irritant.
[0004] Specifically, before the hardened body starts to harden, the mixing materials are mixed to improve workability, including the ease of pouring the material (fluidity) and resistance to material separation, and to prevent or suppress temperature cracks until hardening, and after hardening, to improve the hardened body's chemical resistance, improve its resistance to sulfuric acid, and suppress the penetration of hydrogen sulfide and carbon dioxide and the intrusion of seawater. Furthermore, from the perspective of efficient use of resources and reducing waste, technology has been developed to use sewage sludge incineration ash as an admixture to replace part or all of ordinary Portland cement, or part of the aggregate.
[0005] Patent Document 1 describes acid-resistant concrete, which is a hardened body made by mixing ground granulated blast furnace slag, which are industrial by-products, fly ash, silica fume, and sewage sludge incineration ash instead of ordinary Portland cement, to which fine and coarse aggregates are added and hardened. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Patent Publication No. 2019 / 172349 Summary of the Invention [Problem to be solved by the invention]
[0007] The performance of hardened concrete, such as the rate at which compressive strength increases with age, is greatly affected by the ingredients used. For this reason, there has been a demand for ingredients that can contribute to improving the performance of hardened concrete.
[0008] The present invention has been made in view of the above circumstances, and has an object to provide a compounding material that solves the above-mentioned problems. [Means for solving the problem]
[0009] The compounding material of the present invention is a compounding material to be compounded into a hardened body, and is characterized in that it is configured so as to promote the occurrence and progress of the hardening reaction in the hardened body by adjusting a material in which the reaction of a latent hydraulic material is inhibited or suppressed by a pozzolanic reactive material. The compounding material of the present invention is characterized in that the material is incineration ash containing any one or any combination of sewage sludge incineration ash, garbage incineration ash, woody biomass incineration ash, metal-containing incineration bottom ash and fly ash, which have the properties of a latent hydraulic material and a pozzolanic reactive material. The compounding material of the present invention is characterized in that the incineration ash has at least a portion of the covering of the substance that inhibits the occurrence of the hardening reaction removed, and is adjusted to a state in which the hardening reaction occurs, thereby promoting the occurrence of strength from the completion of mixing and pouring of the hardened body until a specified material age. The compounding material of the present invention is characterized in that the sewage sludge incineration ash contains sewage sludge incineration ash that has been classified to have a median particle size of 20 μm to 30 μm, and then crushed using a wet or dry crushing device to have a particle size of 5 μm or less. The method for preparing a mixed material of the present invention is characterized in that incineration ash is crushed to remove at least a portion of the covering of the pozzolanic reactive substance that inhibits the onset of the hardening reaction, thereby exposing the latent hydraulic substance that quickly initiates the reaction. The method for preparing the compounding material of the present invention is characterized in that the incineration ash includes any one or any combination of sewage sludge incineration ash, garbage incineration ash, woody biomass incineration ash, metal-containing incineration bottom ash and fly ash. The method for producing a hardened body of the present invention is characterized in that a material in which the onset of the reaction of a latent hydraulic material is inhibited or suppressed by the pozzolanic reactive material is adjusted to be constituted as a mixed material that promotes the onset and progress of the hardening reaction in the hardened body, and is mixed so as to promote the onset and progress of the hardening reaction in the hardened body from the completion of mixing and pouring into the hardened body. The method for producing a hardened body of the present invention is characterized by promoting the onset and progression of the hardening reaction of the hardened body, thereby avoiding low strength when the material is young after casting and the delay in strength increase that accompanies the progression of the material's age. The hardened body of the present invention is characterized in that it contains a compounding material that is prepared by adjusting a material in which the reaction of a latent hydraulic material is inhibited or suppressed by a pozzolanic reactive material, and that is configured to promote the onset and progress of the hardening reaction in the hardened body. The hardened body of the present invention is characterized in that the mixed materials contain sewage sludge incineration ash classified to have a median particle size of 20 μm to 30 μm, and sewage sludge incineration ash crushed to a particle size of 5 μm or less using a wet or dry crushing device, so that the ash replaces 5 to 20% of the fine aggregate by weight, based on a water binder ratio of 30 to 45% and a fine aggregate ratio of 45 to 50%. Effect of the Invention
[0010] According to the present invention, a mixing material can be provided that is a latent hydraulic material and / or a pozzolanic reactive material and is configured to promote the onset and progress of the hardening reaction in the hardened concrete, thereby contributing to improving the performance of the hardened concrete, such as the rate of increase in compressive strength with age. [Brief description of the drawings]
[0011] [Figure 1] 1 is a graph showing the age and compressive strength of test specimens when SA according to a comparative example of the present invention is mixed and when it is not mixed. [Diagram 2] 1 is a graph showing the improvement in the age, compressive strength, and compressive strength development of a test specimen when SA according to an embodiment of the present invention is mixed and when it is replaced with SA1. [Diagram 3] 1 is a graph showing the improvement effect on material age, compressive strength, and compressive strength development when the amount of SA1 mixed in an embodiment of the present invention is changed. [Figure 4] 1 is a graph showing the age and compressive strength of test specimens prepared by centrifugal compaction according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] <Embodiment> The inventors of the present invention have been conducting intensive experiments and developments on the types and combinations of other materials to be mixed with incineration ash in concrete and their mixing ratios as technical developments for mixing materials to be mixed as admixtures for hardened concrete or as hardening materials for hardened concrete. Furthermore, they have been studying the mixing ratios of cement or hardening materials as a whole and their ratios to the total weight. In the course of these processes, the inventors discovered that the hardening reaction can be promoted by physically adjusting the incineration ash itself as a mixing material, adjusting a material in which the reaction of the latent hydraulic material is inhibited or suppressed by the pozzolanic reactive material, and configuring it so as to promote the onset and progress of the hardening reaction in the hardened body. They then discovered that by mixing this mixing material into concrete, the rate at which the compressive strength increases with age after mixing and pouring increases, and thus the present invention was completed. Hereinafter, the details of the embodiments of the compounded material and the hardened product of the present invention will be described.
[0013] (compounding material) The mixing material according to the present embodiment is a mixing material to be mixed into the hardened body, and is characterized in that the material in which the reaction of the latent hydraulic material is inhibited or suppressed by the pozzolanic reactive material is adjusted to promote the occurrence and progress of the hardening reaction in the hardened body. Among them, the latent hydraulic material is a material containing a latent hydraulic substance that causes a latent hydraulic reaction to harden in the presence of moisture, as described above. In addition to this, in this embodiment, materials that cause reactions that cause hardening by other hydration may also be included in the latent hydraulic material. On the other hand, the pozzolanic reactive material is a material containing a pozzolanic reactive substance that causes a pozzolanic reaction that hardens in response to the stimulation of alkali that dissolves in water when ordinary Portland cement or mixed cement is kneaded with water. This pozzolanic reaction occurs after the hydration reaction and the latent hydraulic reaction. Also, the mixed cement is a cement in which a part of ordinary Portland cement, such as blast furnace cement, fly ash cement, or sulfate resistant cement, is replaced with another admixture.
[0014] In addition, the mixture material according to this embodiment contains the above-mentioned latent hydraulic material and / or pozzolanic reactive material so as to promote the onset and progress of the hardening reaction so as to promote the increase in strength from immediately after mixing and pouring in the hardened concrete body until demolding and a predetermined period thereafter, and also at any age after the predetermined period. This predetermined period may be a period when the material is still young after demolding, and may be, for example, from the day of demolding to a few days.
[0015] Specifically, the compounding material according to the present embodiment may be incineration ash containing any one or any combination of sewage sludge incineration ash, garbage incineration ash, woody biomass incineration ash, and main ash and fly ash of metal-containing incineration ash having the properties of a latent hydraulic material and / or a pozzolanic reactive material. That is, the incineration ash according to the present embodiment preferably contains fly ash in addition to the main ash of sewage sludge incineration ash, garbage incineration ash, woody biomass incineration ash, and metal-containing incineration ash other than these.
[0016] More specifically, the incineration ash according to this embodiment is preferably sewage sludge incineration ash and garbage incineration ash containing fly ash, in addition to incineration bottom ash containing a variety of substances such as Si, Ca, P, Al, Fe, Mn, and K. In addition, the incineration ash according to this embodiment is physically adjusted so that, when used as an admixture or material for hardened concrete, it causes either or both of a latent hydraulic reaction and a pozzolanic reaction as the above-mentioned latent hydraulic material and / or pozzolanic reaction material.
[0017] Here, as a physical adjustment of the incineration ash according to the present embodiment, it is preferable to remove at least a part of the cover of the substance that inhibits the onset of the hardening reaction, to make the incineration ash in a state in which the hardening reaction occurs. In the case of incineration ash, such a cover of the substance that inhibits the onset of the hardening reaction may be a cover of a pozzolanic reactive substance, as described below. This pozzolanic reactive substance inhibits or suppresses the onset of latent hydraulic reactions, etc., which rapidly initiate a hardening reaction.
[0018] More specifically, in the mixed material according to the present embodiment, by crushing the incineration ash, it is possible to remove at least a part of the covering of the pozzolanic reactive substance. This makes it possible to expose the latent hydraulic substance, which reacts quickly, underneath the covering of the incineration ash. This makes it possible to promote the development of strength from the completion of mixing and pouring the hardened body until the specified material age.
[0019] More specifically, in the compounding material according to this embodiment, the sewage sludge incineration ash may include sewage sludge incineration ash that has been classified to have an average particle diameter (hereinafter referred to as "particle size") of 20 μm to 30 μm as a median value, and that has been crushed in a wet or dry crushing device to have a particle size of 5 μm or less.
[0020] For example, in this embodiment, the sewage sludge incineration ash that is mixed into concrete as an admixture or that is itself used as a hardening material for the hardened body is preferably made by crushing the incineration ash of an industrial by-product, including super ash (hereinafter referred to as "SA"), which is sludge incineration ash that has been subjected to particle size adjustment by classification, as described in Patent Document 1. Here, the main chemical components of the SA according to this embodiment are a mixture mainly composed of Si, Al, and Ca compounds, as shown in Table 1 below.
[0021] [Table 1]
[0022] Unlike that of Patent Document 1, the SA according to this embodiment is not crushed, and may be obtained by classifying particles having a median particle size of 20 μm to 30 μm using a filter or the like. The SA having a particle size of 20 μm to 30 μm that has not been crushed has a layer structure, and as described above, the latent hydraulic substance is covered with a cover of pozzolanic reactive substances. Specifically, the surface of the classified and uncrushed SA is surrounded (covered) by compounds such as Si and Al, which are pozzolanic reactive substances that require the stimulation of alkali in addition to water to manifest hardening. For this reason, if SA is mixed directly into concrete, the pozzolanic reactive substances on the surface will react and harden by the pozzolanic reaction, as with ground granulated blast furnace slag. The pozzolanic reaction is a slower-acting reaction than the latent hydraulic reaction, so the strength of the hardened concrete increases slowly.
[0023] In contrast, in this embodiment, it is preferable to use a wet or dry crushing device to crush the SA and remove at least a part of the covering of the pozzolanic reactive substance that inhibits the onset of the hardening reaction. As a result, the Ca compound of the latent hydraulic substance that has latent hydraulic properties that harden in the presence of water and is inside the covering of the pozzolanic reactive substance of the SA is exposed. Since the latent hydraulic substance reacts more quickly than the pozzolanic reactive material, exposing the latent hydraulic substance in this way makes it possible to promote hardening immediately after mixing.
[0024] Specifically, as a mixing material according to this embodiment, the particle size of the incineration ash such as sewage sludge incineration ash to be mixed into the hardened concrete body is 5 μm or less, or the specific surface area is 4,600 g / mm 2 In this embodiment, SA was crushed by a wet or dry crushing device to a particle size of 5 μm or less (hereinafter referred to as "SA1"). Sewage sludge incineration ash such as SA is crushed to a particle size of 5 μm or less or a specific surface area of 4,600 g / mm 2 In other words, as in SA1, the sewage sludge incineration ash is crushed to a particle size of 5 μm or less, or a specific surface area of 4,600 g / mm 2By crushing as described above, the covering of the pozzolanic reactive material can be partially or completely removed.
[0025] By configuring in this way and promoting a rapid reaction with water, it is possible to promote the onset and progress of the hardening reaction in the hardened body during the time from mixing and pouring to removal from the form, thereby increasing the strength of the concrete. As a result, it is possible to prevent the occurrence of delays in the development of strength in the hardened body and to increase the rate of increase in compressive strength with the progression of material age. In other words, SA1 can improve the delay in the development of early strength, which has been an issue with concrete containing SA, as shown in the examples described later.
[0026] Furthermore, as shown in the examples below, when SA1 is actually mixed into hardened concrete, the strength of the hardened concrete can be increased immediately after mixing and demolding. More specifically, it has the effect of increasing the strength at 0 days after demolding. This effect is due to the fact that latent hydraulic substances, which have the property of rapidly undergoing a hardening reaction when reacting with water, undergo a hardening reaction when they come into contact with water immediately after mixing. In addition, it is thought that the increase in the speed of compressive strength is also related to the fact that the particle size of SA, which is sewage sludge incineration ash, is reduced by crushing, or the specific surface area is increased. In this way, the compressive strength at 0 day age, which is immediately after the completion of mixing and pouring and removal from the formwork, can be improved according to the amount of SA1 added.
[0027] Furthermore, by mixing SA1 into concrete, as shown in the examples described later, it is possible to increase the rate of increase in the compressive strength of concrete from age 0 to age 7 days, which is the above-mentioned predetermined period. This makes it possible to solve the problem of slow hardening over a predetermined period that has been an issue with conventional SA. Furthermore, it is possible to increase the compressive strength after age 7 days. In other words, it is possible to improve the speed of strength development of the hardened body and the compressive strength at a set predetermined age, such as 7 days, 14 days, or 28 days.
[0028] Here, as shown in the examples described later, the increase in compressive strength at 0 days and at 7 days or more improves as the amount of SA1 mixed to replace part of the fine aggregate increases in the order of 0%, 10%, and 15% of the fine aggregate weight. Preliminary experiments by the present inventors have shown that the replacement with SA1 is preferably 5 to 20% of the fine aggregate weight. By mixing SA1 in this ratio, the properties of the concrete at the time of mixing can be improved.
[0029] In addition, the particle size or specific surface area, mixing ratio, etc. of the incineration ash such as sewage sludge incineration ash in this embodiment may be appropriately changed based on the target compressive strength due to the age of the hardened concrete body and the rate of increase in compressive strength, etc. In addition, as the compounding material according to the present embodiment, it is possible to use a material other than incineration ash by configuring it as a latent hydraulic material and / or a pozzolanic reactive material so as to promote the occurrence and progress of the hardening reaction in the hardened body. For example, it is possible to use a material other than incineration ash, such as waste ceramic powder containing silicon and calcium. Or, even if it is incineration ash such as the above-mentioned SA, it may be configured to promote the occurrence and progress of the hardening reaction in the hardened body by including other compounding materials. For example, the mixing material according to this embodiment may contain, in addition to incineration ash, a latent hydraulic admixture that is effective in increasing the strength of the hardened concrete body, a pozzolanic reactive admixture, and / or a mixing material having properties of both.
[0030] (hardened body) The method for producing a hardened body according to this embodiment is a method for producing a hardened concrete body, characterized in that a latent hydraulic material and / or a pozzolanic reactive material, which is configured to promote the onset and progress of the hardening reaction in the hardened body, is mixed in such a way as to promote the onset and progress of the hardening reaction in the hardened body from the completion of mixing and pouring into the hardened body.
[0031] Specifically, the method for producing a hardened body according to this embodiment may promote the occurrence and progress of the hardening reaction of the hardened body, thereby avoiding low strength when the material is young after casting and delay in strength increase with the progression of the material age. Here, as described above, it is possible to use incineration ash or the like as an admixture or material for the hardened body as a latent hydraulic material and / or a pozzolanic reactive material that is effective in increasing the strength of the hardened body of the concrete, which is the mix material according to this embodiment. This makes it possible to improve the strength during the period from casting into the mixing formwork to removal from the form, and to increase the strength for a predetermined period from immediately after removal from the form.
[0032] More specifically, in the hardened body according to this embodiment, the mixed materials may contain sewage sludge incineration ash that has been classified to have a median particle size of 20 μm to 30 μm, and that has been crushed to a particle size of 5 μm or less using a wet or dry crushing device, so that it can replace 5 to 20% of the fine aggregate, based on a water binder ratio of 30 to 45% and a fine aggregate ratio of 45 to 50%.
[0033] By configuring in this way, the strength of the hardened concrete can be increased during the period from mixing and pouring to demolding, the rate of increase in compressive strength over a specified period can be increased, and the strength after the specified period can also be increased. This can eliminate the delay in increase in compressive strength caused by mixing SA, for example. Furthermore, it is possible to ensure workability, suppress thermal cracks, and improve acid resistance, seawater resistance, and carbon dioxide permeation resistance after hardening.
[0034] In particular, when incineration ash derived from waste is mixed as an admixture into the hardened concrete body as a compounding material according to this embodiment, it is possible to avoid a decrease in workability during the mixing stage before hardening. In addition, it is also possible to avoid or improve delays in strength development during the hardening stage. In particular, when sewage sludge incineration ash is used as an admixture or material for the hardened concrete body, it is possible to utilize the sewage sludge incineration ash by accelerating the strength development and strength increase, which promotes the effective use of resources and contributes to improving the performance of the hardened concrete body.
[0035] The hardened body according to this embodiment may contain other industrial by-products such as fly ash, silica fume, and ground granulated blast furnace slag, as in the acid-resistant concrete described in Patent Document 1.
[0036] The fly ash according to this embodiment is polazon coal ash (fly ash) for concrete, which is collected by a dust collector from pulverized coal combustion in a thermal power plant. Fly ash is mainly composed of silica and alumina, and hardens by a pozzolanic reaction that produces calcium silicate hydrate and the like in an alkaline atmosphere when an alkaline stimulant is used.
[0037] The silica fume according to this embodiment is mostly amorphous and spherical silica (SiO2) etc., which is collected as dust in the exhaust gas when ferrosilicon etc. are produced in an arc type electric furnace. Silica fume is a material with a spherical shape like fly ash, but its particle size is even smaller than that of fly ash.
[0038] The ground granulated blast furnace slag according to this embodiment is a fine powder produced as a by-product in the process of producing pig iron. Ground granulated blast furnace slag has a "latent hydraulic property" that hardens by generating calcium silicate hydrate and calcium aluminate hydrate, and hardens when moisture is supplied and an alkaline stimulant is added. It is the material that mainly generates strength in the hardened body according to this embodiment.
[0039] In addition to these, materials related to the densification according to this embodiment may also be used, such as fine volcanic glass powder for concrete, fine waste glass powder, and concrete materials that harden in an alkaline atmosphere.
[0040] Furthermore, the hardened body according to the present embodiment may contain any one or any combination of potassium hydroxide, potassium carbonate, and hydrated lime as an alkaline irritant. When potassium carbonate dissolves in water, it decomposes into KOH and H2CO3 through hydrolysis, and KOH is further converted into K + and OH - This ionizes the water to OH - It is considered that the hydroxide ions liberate the hydroxide ions and act as an inducer of latent hydraulic reactions and pozzolanic reactions. In other words, in this embodiment, it is possible to use a material that supplies hydroxide ions during the reaction of the hardened body in a broad sense. Furthermore, it is also possible to use hydroxide ion compound materials other than those mentioned above.
[0041] The hardened body according to this embodiment may be produced by compacting using centrifugal molding, vibrating molding, or by pouring at the site.
[0042] In addition, as the industrial by-product of this embodiment, it is possible to use other materials than the above-mentioned fly ash, ground granulated blast furnace slag, sewage sludge incineration ash, and silica fume. For example, it is possible to use incineration ash from a biomass power plant, soot dust, residues from mineral refining, etc., which contain Ca, Si, various inorganic metals, etc. In addition, it is possible to use materials other than the above-mentioned SA1 as the sewage sludge incineration ash. In addition to slaked lime, alkali metal hydroxides such as sodium hydroxide, alkali metal hydrates, gypsum, etc. can also be used as the alkaline stimulant.
[0043] In addition to providing the mixing material according to this embodiment itself, it may be provided as a composition for a hardened body in the form of a premix or mixture (hereinafter simply referred to as a "mixture") obtained by removing water from each material mixed by the above-mentioned mixing method for a hardened body. This mixture may be provided in a form further containing coarse aggregate, sand contained in fine aggregate, and a high-performance water reducing agent. In this case, the mixing ratio may be changed depending on whether the material is precast or cast in place. EXAMPLES
[0044] Hereinafter, examples of the present invention will be described with reference to the drawings. However, the present invention is not limited to these examples.
[0045] (Materials and properties of hardened body) Table 2 below shows the material name, type and physical properties (properties) of the hardened body, density, specific surface area, and particle size.
[0046] [Table 2]
[0047] The SA, which is the sludge incineration ash according to this embodiment, is sewage sludge incineration ash produced at a sewage treatment plant of the Tokyo Metropolitan Government Bureau of Sewerage, and classified using a bag filter to have a median particle size of 20 μm to 30 μm. In this embodiment, the average particle size of SA is 23 μm. SA1 was prepared by pulverizing the SA in a wet ball mill to a particle size of 5 μm or less. In this example, the SA was placed in a 500 ml cylindrical container containing 10 zirconia (ZrO2) spheres with a diameter of 15 mm and 5 spheres with a diameter of 10 mm, together with water that was 100% by weight of the SA, and mechanically pulverized.
[0048] (Composition of mixing materials, composition, and concrete mix example) In this example, the materials shown in Table 2 were mixed while taking into consideration the particle size or specific surface area of the SA and SA1 materials, which are sewage sludge incineration ash to be mixed into concrete, and the differences in the speed of the hardening reaction of the materials. The materials were cured in air in a constant temperature and humidity room at an air temperature of 20°C and a relative humidity of 60% until the material ages reached 0 days (at the time of removal from the form), 7 days, 14 days, and 28 days, and then compression tests were conducted at the specified material ages. As a result, the strength increase after demolding of the concrete of this embodiment was compared over time, and the improvement in the decrease in strength of concrete at age 0 days and the delayed increase in strength from age 0 to age 7 days due to the incorporation of sewage sludge incineration ash according to the present invention were measured, as well as the strength of concrete at age 28 days.
[0049] Table 3 below shows examples of the concrete mixes used in this embodiment. 3 The weight to be mixed per unit is indicated.
[0050] [Table 3]
[0051] (Production and testing of hardened concrete) For the hardened concrete of this example, SA or SA1 was used, and part of the fine aggregate was replaced with ordinary Portland cement in the concrete according to the composition shown in Table 3. The concrete was then poured into a cylindrical specimen formwork with a diameter of 100 mm and formed using vibration or centrifugal force. After that, the concrete was demolded after 24 hours to prepare a cylindrical specimen. The time of removal from the form was set as day 0, and the concrete was then cured in air in a constant temperature and humidity room at a temperature of 20°C and a relative humidity of 60% until the specified ages of 7, 14, and 28 days. Tests were then conducted on the 0, 7, 14, and 28 days using a method similar to the compression test method for concrete specified in JIS A1108. SA1 in Tables 2 and 3 is an embodiment, and SA is a comparative example.
[0052] (result) Fig. 1 shows the effect of mixing SA as a comparative example. Specifically, it is a graph showing the compressive strength at age 0 after demolding and the progress of compressive strength increase over time for Mixing Example 1, a comparative example in which SA was not mixed, and Mixing Example 4, a comparative example in which 10% of the fine aggregate weight was replaced with SA and mixed into the concrete. The vertical axis shows the compressive strength (N / mm 2 ) and the horizontal axis shows the age of the material (days).
[0053] As a result, the compressive hardness of Mixture Example 4, which contains SA, was lower than that of Mixture Example 1, which does not contain SA, at 0 days and 7 days. The decrease in compressive strength of Mixture Example 4, which contains SA, was 0.2 N / mm at 0 days after demolding. 2 However, at 7 days, it is 0.8N / mm 2 At 14 days, the strength of the concrete in Mix 4, which contains SA, was 1.9 N / mm 2 It showed high compressive strength. In other words, when SA was mixed into concrete as an admixture, the decrease in compressive strength after demolding from 0 days to 7 days was an issue.
[0054] FIG. 2 shows the time series of the increase in compressive strength from 0 days to 28 days after demolding for Mixing Example 4, a comparative example in which SA was replaced with fine aggregate and 10% of the fine aggregate was mixed, and Mixing Example 2, an example in which SA1 was replaced with fine aggregate and 10% of the fine aggregate was mixed. The vertical axis shows the compressive strength (N / mm 2 ) and the horizontal axis shows the age of the material (days).
[0055] In comparison with Mixture Example 4, Mixture Example 1 had a strength of 3.1N / mm 2 , 3.2N / mm at 7 days 2 , 5.0N / mm at 14 days 2 , and at 28 days, it was 5.1N / mm 2 It was confirmed that the compressive strength of Mixture Example 2, which contained SA1, was higher at all ages than that of Mixture Example 4, which contained SA, and the improvement effect of this embodiment was confirmed.
[0056] As a result, compared to Blend Example 4, which was mixed with SA as a comparison example, Blend Example 2, which was mixed with SA1 as an embodiment, had higher compressive strength at 0 days, which is the period from immediately after mixing until demolding, and from 0 days to 7 days, and it was confirmed that there was an improvement in the rate of increase in compressive strength due to the progression of material age during this period (hereinafter referred to as the "compressive strength increase rate").
[0057] The rate of increase in compressive strength from age 0 to age 7 days was α 20 =1.77N / mm 2 / day. In addition, in Example 4, where the same amount of SA was mixed, α 40 =1.75N / mm 2 The rate of increase in compressive strength from age 7 to age 14 days was α 27 =0.99N / mm 2 / day. In addition, in Example 4, α 47 =0.75N / mm 2 / day, and the rate of increase in compressive strength from 14 days to 28 days was α 214 =0.59N / mm 2 / day, and in Mixture Example 4, α 414 =0.56N / mm 2 It was confirmed that the increase in compressive strength after 0 days of age was greater for concrete containing SA1 than for AS. As a result, by mixing SA1, which is made by crushing and micronizing SA, instead of SA, it is possible to improve the delay in the increase in strength of concrete from age 0 to age 7 days.
[0058] Figure 3 shows the time series of changes in material age and compressive strength for Mix Example 1, which does not contain SA1, Mix Example 2, which uses 10% of the fine aggregate weight instead of SA1, and Mix Example 3, which uses 15% of the fine aggregate weight instead of SA1. The vertical axis shows compressive strength (N / mm 2 ) and the horizontal axis shows the age of the material (days).
[0059] The compressive hardness at 0 days was 36.8N / mm for Mix Example 1, which does not contain SA1. 2 , and 39.7N / mm for Example 2 with 10% mixture. 2, and 42.8N / mm for Example 3 with a mixing ratio of 15%. 2 The compressive strength after 7 days of age was 52.2N / mm for Mix Example 1, which does not contain SA1, at 14 days of age. 2 , and 59.0N / mm for Example 2 with 10% mixture. 2 , and 62.9N / mm for Example 3 with a mixing ratio of 15%. 2 The difference in compressive strength between Mixture Example 1 and Mixture Example 2 was 6.8N / mm 2 The difference between compounding examples 1 and 3 was 10.7 N / mm 2 As a result, it was confirmed that the concrete containing SA1 exhibited an increase in compressive strength over time compared to the concrete not containing SA1.
[0060] At 28 days, the strength of the material was 54.7N / mm 2 , and 63.1N / mm for Example 2 with 10% mixture. 2 , and 65.4N / mm for Example 3 with a mixing ratio of 15%. 2 Furthermore, the difference in compressive strength between Mixture Example 1 and Mixture Example 2 was 8.4N / mm 2 The difference in compressive strength between Mixture Example 1 and Mixture Example 3 was 11.2N / mm 2 Thus, compared to the difference in compressive strength observed at 14 days of age, the difference in compressive strength increased depending on whether SA1 was added or not. In other words, it was confirmed that the difference in compressive strength caused by the difference in whether SA1 was added or not increases as the material ages.
[0061] As shown in Figure 3, the rate of increase in compressive strength from age 0 to age 7 days was α 20 =1.77N / mm 2 / day, and Mixture Example 3 is α 30 =2.08N / mm 2 That is, the rate of increase in compressive strength increased according to the amount of SA1 added.
[0062] Thus, the addition of SA1 increased the rate of increase in compressive strength during the period from mixing and pouring to removal from the form, which is the compressive strength at day 0. In other words, it was confirmed that the increase in compressive strength after day 7 was promoted depending on the amount of SA1 added.
[0063] Figure 4 shows the compressive strength of specimens mixed with SA1 and centrifuged for use in the manufacture of precast concrete products, from age 0 to age 14. The vertical axis shows the compressive strength (N / mm 2 ) and the horizontal axis shows the age of the material (days).
[0064] Even when concrete is compacted by centrifugal compaction, the strength at age 0 is 42.8 N / mm for Mix Example 1 with 0% SA1, the same as concrete compacted by vibration compaction. 2 , 10% compounding example 2 is 44.3N / mm 2 , 15% compounding example 3 is 54.7N / mm 2 It was confirmed that the compressive strength increases according to the amount of SA1 mixed in. At 14 days, the compressive strength was 59.0 N / mm for Mix Example 1, which had 0% SA1 mixed in. 2 , 10% compounding example 2 is 68.1N / mm 2 , 15% compounding example 3 is 71.0N / mm 2 It was confirmed that the compressive strength increased in proportion to the amount of SA1 mixed.
[0065] In this way, it was confirmed that not only the vibration compaction method but also the centrifugal compaction method has the effect of improving the compressive strength at age 0 days and increasing the compressive strength from age 0 to age 14 days. In other words, it was confirmed that the strength increases according to the amount of admixture and the age of the material even in the test specimens made by centrifugal compaction.
[0066] As a result, it was confirmed that the improvement in compressive strength at day 0 of concrete mixed with SA1, which is made by crushing and micronizing SA made from sewage sludge incineration ash to adjust its particle size, and the increase in compressive strength from day 0 to day 14 are not affected by differences in the vibration method, centrifugation, or other formation methods used to mix, pour, and compact the concrete.
[0067] It goes without saying that the configurations and operations of the above-described embodiments are merely examples and can be modified as appropriate without departing from the spirit and scope of the present invention.
Claims
1. A compounding material to be compounded into a hardened body, A material in which the reaction of a latent hydraulic material is inhibited or suppressed by a pozzolanic reactive material is prepared, and the material is configured to promote the occurrence and progress of the hardening reaction in the hardened body. A compounded material characterized by:
2. The material is incineration ash including any one or any combination of sewage sludge incineration ash, garbage incineration ash, woody biomass incineration ash, and metal-containing incineration ash, which has the properties of a latent hydraulic material and a pozzolanic reactive material. The composition of claim 1 .
3. The incineration ash is adjusted to a state in which the hardening reaction is caused to occur by removing at least a part of the covering of the substance that inhibits the occurrence of the hardening reaction, and promotes the occurrence of strength from the completion of mixing and pouring of the hardened body until a predetermined material age.
3. The composition of claim 2.
4. The sewage sludge incineration ash includes sewage sludge incineration ash classified to have a median particle size of 20 μm to 30 μm, which is crushed to a particle size of 5 μm or less using a wet or dry crushing device.
3. The composition of claim 2.
5. The incineration ash is crushed to remove at least a part of the covering of the pozzolanic reactive material that inhibits the hardening reaction from occurring, thereby exposing the latent hydraulic material that reacts quickly. A method for preparing a compounded material comprising the steps of:
6. The incineration ash includes any one or any combination of sewage sludge incineration ash, garbage incineration ash, woody biomass incineration ash, and metal-containing incineration ash, including main ash and fly ash.
6. The method for preparing a compounded material according to claim 5.
7. A material in which the reaction of a latent hydraulic material is inhibited or suppressed by a pozzolanic reactive material is adjusted so as to be constituted as a mixed material that promotes the onset and progress of the hardening reaction in the hardened body; It is blended so as to promote the occurrence and progress of the hardening reaction in the hardened body after the completion of mixing and pouring into the hardened body. A method for producing a hardened body comprising the steps of:
8. By promoting the occurrence and progress of the hardening reaction of the hardened body, it is possible to avoid low strength when the material is still young after driving and the delay in strength increase that accompanies the progression of the material's age. The method for producing a cured body according to claim 7 .
9. The present invention includes a compounding material that is configured to adjust a material in which the reaction of a latent hydraulic material is inhibited or suppressed by a pozzolanic reactive material, and to promote the onset and progress of the hardening reaction in the hardened body. A hardened body characterized by the above-mentioned.
10. The mixed material contains sewage sludge incineration ash, which has been classified to have a median particle size of 20 μm to 30 μm, and sewage sludge incineration ash crushed to a particle size of 5 μm or less using a wet or dry crushing device, so that it can replace 5 to 20% of the weight of the fine aggregate, based on a water binder ratio of 30 to 45% and a fine aggregate ratio of 45 to 50%. The hardened body according to claim 9 .
Citation Information
Patent Citations
Acid-resistant concrete, precast concrete, and method for producing acid-resistant concrete
WO2019172349A1